Neuronal avalanche dynamics and functional connectivity elucidate information propagation in vitro - Heiney, Kristine; Huse Ramstad, Ola; Fiskum, Vegard; Sandvig, Axel; Sandvig, Ioanna; Nichele, Stefano (Frontiers in Neural Circuits, 2022)
Cascading activity is commonly observed in complex dynamical systems, including networks of biological neurons, and how these cascades spread through the system is reliant on how the elements of the system are connected and organized. In this work, we studied networks of neurons as they matured over 50 days in vitro and evaluated both their dynamics and their functional connectivity structures by observing their electrophysiological activity using microelectrode array recordings. Correlations were obtained between features of their activity propagation and functional connectivity characteristics to elucidate the interplay between dynamics and structure. The results indicate that in vitro networks maintain a slightly subcritical state by striking a balance between integration and segregation. Our work demonstrates the complementarity of these two approaches---functional connectivity and avalanche dynamics---in studying information propagation in neurons in vitro, which can in turn inform the design and optimization of engineered computational substrates.